TIMP-3 mRNA is not overexpressed in Sorsby fundus dystrophy. - Chong, N; Kvanta, A; Seregard, S; Bird, A; Luthert, P; Steen, B (2003)
PURPOSE: To assess the expression of MMP (matrix metalloproteinase)-2 and -9 and TIMP (tissue inhibitors of metalloproteinases)-1, -2, and -3 in Sorsby fundus dystrophy. DESIGN: Cliniciopathological report. METHODS: A donor eye with a confirmed S181C mutation in the TIMP-3 gene and an age-matched normal donor eye were studied using in situ hybridization technique with MMP -2 and -9 and TIMP -1, -2, and -3 probes. RESULTS: There is a reduction of mRNA expression of MMP-2 and TIMP-3 in the Sorsby retinal pigment epithelium cells. CONCLUSIONS: Increased expression of TIMP-3 mRNA does not cause accumulation of TIMP-3 in the Bruch membrane of Sorsby fundus dystrophy nor is it likely to cause age-related macular degeneration.